A simulated annealing for a daily operating room scheduling problem under constraints of uncertainty and setup. Issue 3 (2nd July 2020) - Abdeljaouad, Mohamed Amine; Bahroun, Zied; Saadani, Nour El Houda; Zouari, Belhassen
Abstract: This article addresses the daily scheduling of surgeries in an operating theatre. The problem consists of a set of surgical operations that have to be scheduled in identical operating rooms. The operations have uncertain durations, require setup activities before and after the surgical act and are assigned to surgeons who have to perform the surgical part. The objective is to find the best sequence of operations in each room in order to minimize the theatre's opening duration (makespan) and the surgeons' waiting times. A stochastic mathematical model and a simulated annealing-based algorithm, where the uncertainty is represented using the sample average approximation technique, are provided. An experimental study carried out on real-sized instances shows that the method's solutions have respectable relative gaps in comparison with lower bounds and optimal solutions.